Phenotypic Heterogeneity of Neutropenia and Gastrointestinal Illness Associated with G6PC3 Founder Mutation. Issue 7 (October 2016) - Glasser, Chana L.; Picoraro, Joseph A.; Jain, Preti; Kinberg, Sivan; Rustia, Evelyn; Gross Margolis, Kara; Anyane-Yeboa, Kwame; Iglesias, Alejandro D.; Green, Nancy S.
Abstract : Severe congenital neutropenia type IV (SCN IV) is a syndrome of severe neutropenia, cardiac and urogenital defects, prominent superficial veins, facial dysmorphism, failure to thrive (FTT), and intermittent thrombocytopenia, caused by a glucose-6-phosphatase catalytic subunit 3 ( G6PC3 ) gene mutation. SCN IV has been linked to glycogen storage disease type 1b as both disorders involve disruption of the glucose-6-phosphatase/glucose-6-phosphate transporter complex, leading to arrested neutrophil maturation. Emerging evidence suggests that neutrophil function plays an important role in intestinal integrity, evidenced by inflammatory bowel disease in certain neutropenic patients. Here, we report 3 unrelated Hispanic males from the Dominican Republic with classic features of SCN IV found to share an identical inherited canonical splice-site mutation of the G6PC3 gene (c.218+1G>A). All 3 patients presented with severe FTT and gastrointestinal manifestations. Two of the patients had significant improvement in growth and resolution of gastrointestional symptoms with initiation of granulocyte colony-stimulating factor. We hypothesize that the gene variant described represents a founder mutation in the Dominican Republic, the first to be described in this geographical region. We discuss the potential associations between neutropenia and gastrointestinal disease with FTT and the role of granulocyte colony-stimulating factor in improving neutrophil count and intestinal integrity and growth.